Ostrea (Turkostrea) Doidoiensis Hasibuan from The Bayah Formation West Jawa: A New Find - Hasibuan, Fauzie (Pusat Survei Geologi, 2006)
A species of Ostreidae conspecific with Ostrea (Turkostrea) doidoiensis Hasibuan from the Middle Eocene Malawa Formation, South SuIawesi, was also discovered from Bayah Formation, Banten, West Jawa. A juvenile form of the taxon is thought to occur in the Nanggulan Formation, Central Jawa, Correlation of the age of the formations is considered. Paleoenvironmental implication of the taxon and its distribution in Indonesia are discussed.Keywords: Ostrea (Turkostrea) doidoensis, Bayah formation, Malawa formation, Middle Eocene, RV (right valve). LV (left valve)